Research regarding the occurrence of new elements for vaulting table performance in women's artistic gymnastics - Nakasone, M. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: More recently a total of 600 elements have been recorded in the Gymnastics Code of Points. However there are few theses on elements of gymnastics history. As such we wonder by whom, when or where these various elements are performed. The purpose of this study was to collate data elements on the Vaulting Table (VT) in women`s artistic gymnastics and to suggest new elements in the future. Methods: The method of study was undertaken by bibliographic analysis. This article refers mainly to journals that were published by the Japan Gymnastic Association, and a list that was made regarding the occurrence of new elements on VT in women`s artistic gymnastics. Results: From the analysis, the author gatherd data regarding various elememts that were performed. For example, the round off, backward handspring and salto stretch (Yurchenko) was performed by YURCHENKO.N in the 1982 Moscow Newscup. A Yurchenko stretch with a double twist was performed by AMANAR.S in the 2000 European Championships. This element is performed by many top women gymnasts. Another example, a sideward handspring with a 1/4 twist and backward tucked salto (Tsukahara) was performed by TURISCHEVA.L in the 1974 World Championships. Additionally, the Tsukahara stretch with a double twist was performed by a Cuban woman gymnast. In recent years, the round off, 1/2 twist and forward handspring and forward stretched salto with a 3/2 twist was performed by CHENG.F in the 2005 World Championships. From 2005 onwards, new elements on the VT in women`s artistic gymnastics were not performed. Discussion: In conclusion, developments of VT elements are greatly influenced by the improvement of apparatus, rules of the era and improved skills of men`s gymnastics. As a result, we have to pay attention to changes to the Men`s Code of Points. In the near future, directions of new occurring elements on the VT may add twists to the existing elements.